The role of sexual expectancies of substance use as a mediator between adult attachment and drug use among gay and bisexual men. (1st August 2015) - Starks, Tyrel J.; Millar, Brett M.; Tuck, Andrew N.; Wells, Brooke E.
Highlights: Anxious and avoidant attachment predicted sexual expectancies of substance use. Sexual expectancies of substance were positively associated with recent drug use. Anxious attachment was indirectly associated with drug use through expectancies. Abstract: Background: Research exploring substance use in gay and bisexual men has increasingly paid attention to interpersonal dynamics and relational concerns associated with the use of substances. The current study explored the role of adult attachment style on drug use as well as the potential mediating role of sexual expectancies of substance use among gay and bisexual men. Methods: Online survey data were gathered from 122 gay and bisexual men across the U.S., with a mean age of 33 years. All participants were HIV-negative and identified their relationship status as single. Survey measures included attachment style, sexual expectancies of substance use, and recent drug use. Results: While neither anxious or avoidant attachment were directly associated with the odds of recent drug use, they were positively associated with sexual expectancies of substance use ( β  = 0.27, p  < 0.01, and β  = 0.21, p  < 0.05) which, in turn, were positively associated with the odds of drug use (expB = 1.09, p  < 0.01). Bootstrapping tests of indirect effects revealed a significant indirect relationship between anxious attachment and drug use through sexual expectancies of substance use ( β  = 0.11, p  < 0.05), but not for avoidant attachment. Conclusions: This study highlights the importance of interpersonal expectancies as motivators for drug use among gay and bisexual men. Sexual expectancies of substance use were associated with drug use and anxious adult attachment was associated indirectly with drug use through these sexual expectancies.